Can women’s empowerment increase animal source food consumption in flood prone areas of Bangladesh? - Theys, Natalie (International Food Policy Research Institute, 2018)
Bangladesh is one of the most flood-prone countries in the world and households located in at-risk areas endure periodic destruction and losses, thus making them worse off than those not prone to flooding. Our paper provides evidence that promoting women’s empowerment could be a promising way to improve quality of life for these at-risk households. Our focus is on the relationship between empowerment and improved dietary quality, specifically through the increased consumption of animal source foods (ASF).